A Psychometric Evaluation of the DSM-IV Criteria for Antisocial Personality Disorder: Dimensionality, Local Reliability, and Differential Item Functioning Across Gender - Paap, Muirne C. S. (Assessment, 2017)
This study aims at evaluating the psychometric properties of the antisocial personality disorder (ASPD) criteria in a large sample of patients, most of whom had one or more personality disorders (PD). PD diagnoses were assessed by experienced clinicians using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, 4th edition, Axis II PDs. Analyses were performed within an item response theory framework. Results of the analyses indicated that ASPD is a unidimensional construct that can be measured reliably at the upper range of the latent trait scale. Differential item functioning across gender was restricted to two criteria and had little impact on the latent ASPD trait level. Patients fulfilling both the adult ASPD criteria and the conduct disorder criteria had similar latent trait distributions as patients fulfilling only the adult ASPD criteria. Overall, the ASPD items fit the purpose of a diagnostic instrument well, that is, distinguishing patients with moderate from those with high antisocial personality scores.